Assessing spatio-temporal land use and land cover changes in Sonbhadra District, Uttar Pradesh - Sunil Kumar Singh; Vishwambhar Nath Sharma (National Geographical Journal of India, 2025)
Land, as a fundamental natural resource, plays a crucial role in supporting both ecological balance and human development. Over the centuries, humans have altered land use patterns to meet growing demands for agricultural and non-agricultural purposes. This study investigates the spatio-temporal dynamics of land use and land cover (LULC) changes in Sonbhadra district, Uttar Pradesh, over a 24-year period from 1995 to 2019. The study area has been classified into nine distinct land use categories, each reflecting varied human-environment interactions. The present study is based primarily on secondary data obtained from satellite imagery, including Landsat data and Google Earth visualizations, supplemented by official records from relevant government departments and field-level surveys. Additionally, primary insights were gathered through interviews and focus group discussions with key stakeholders such as farmers, landowners, and local administrative officials. The research provides critical insights into the drivers and consequences of land transformation and emphasizes the importance of sustainable land-use planning for regional development.